Crystal structure of ethyl 5′′-fluoro-2′′, 3-dioxo-6′, 7′, 8′, 8a'-tetrahydro-2′H, 3H, 5′H-dispiro[benzo[b]thiophene-2, 1′-indolizine-3′, 3′′-indoline]-2′-carboxylate. (March 2015) - Raja, R.; Govindaraj, J.; Suresh, M.; Raghunathan, R.; SubbiahPandi, A.
No abstract available